Financial Performance of Local Governments: The Effects of Disaster Risk - Anggriani, Nova; Chairil Furqan, Andi; Sukmawati Yuniar, Latifah; Megawati Sitorus, Shinta (KnE Social Sciences, 2024)
Financial performance is a measure of assessing the sustainability of an organization. This study aims to analyze how disaster risk impacts local governments’ financial performance as measured by the Disaster Risk Index (DRI). This study uses data from Local Governments in Indonesia for 2015-2021 with a total sample size of 3766 observations. The results show that the DRI negatively impacts the level of local autonomy, financial flexibility, and service solvency. However, the DRI has no bearing on short-term solvency. The results are robust to different measurements of the DRI, whether using scores or DRI categories, particularly the negative impact of the DRI on the level of regional autonomy and service solvency. These findings have implications for efforts to improve the financial performance of local governments and reduce disaster risk (DRR). Therefore, as a strategy to enhance financial performance while maintaining regional financial sustainability, local governments need tot establish policies and disaster mitigation programs oriented toward disaster risk reduction. Keywords: DRI, financial performance, level of regional autonomy, financial flexibility, service solvency